Dual effects of glucose on the cytosolic Ca2+ activity of mouse pancreatic beta-cells. - Rorsman, P; Abrahamsson, H; Gylfe, E; Hellman, B (1984)
The cytosolic Ca2+ activity of mouse pancreatic beta-cells was studied with the intracellular fluorescent indicator quin2 . When the extracellular Ca2+ concentration was 1.20 mM, the basal cytosolic Ca2+ activity was 162 +/- 9 nM. Stimulation with 20 mM glucose increased this Ca2+ activity by 40%. In the presence of only 0.20 mM Ca2+ or after the addition of the voltage-dependent Ca2+ -channel blocker D-600, glucose had an opposite and more prompt effect in reducing cytosolic Ca2+ by about 15%. It is concluded that an early result of glucose exposure is a lowering of the cytosolic Ca2+ activity and that this effect tends to be masked by a subsequent increase of the Ca2+ activity due to influx of Ca2+ through the voltage-dependent Ca2+ channels.